2021
DOI: 10.21203/rs.3.rs-143399/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organ Specific Responses to First-line Lenvatinib Plus Anti-PD-1 Antibodies in Patients With Unresectable Hepatocellular Carcinoma: a Retrospective Analysis

Abstract: BackgroundWe evaluated organ-specific response rates (OSRRs) to first-line lenvatinib plus anti-PD-1 antibodies in patients with advanced hepatocellular carcinoma (HCC).MethodsThis retrospective analysis included Chinese patients with unresectable/advanced HCC who received first-line lenvatinib (8 mg/day) plus ≥3 infusions of anti-PD-1 antibodies between October 2018 and May 2020. Tumor and macrovascular tumor thrombi (MVTT) treatment responses were evaluated every 2 months using RECIST v1.1. The overall respo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Preoperative targeted immunotherapy allowed more patients with advanced disease to attempt radical surgical resection, thereby greatly prolonging the OS of advanced HCC [29,30]. Evidence from several cohorts illustrates that the combination of targeted therapy and immune therapy, optionally augmented by additional interventions, has yielded improved ORR of 30.0%-80.6% and increased conversion surgery rates of 10.0%-42.4% in patients with advanced HCC [24,26,[31][32][33]. However, little attention has been paid to the difference in postoperative outcomes between upfront surgery and surgical resection after neoadjuvant targeted immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative targeted immunotherapy allowed more patients with advanced disease to attempt radical surgical resection, thereby greatly prolonging the OS of advanced HCC [29,30]. Evidence from several cohorts illustrates that the combination of targeted therapy and immune therapy, optionally augmented by additional interventions, has yielded improved ORR of 30.0%-80.6% and increased conversion surgery rates of 10.0%-42.4% in patients with advanced HCC [24,26,[31][32][33]. However, little attention has been paid to the difference in postoperative outcomes between upfront surgery and surgical resection after neoadjuvant targeted immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported prolonged OS, tumor downgrading, lower risk of postoperative recurrence, and tolerable AEs associated with targeted immunotherapy [23][24][25]. HCC with macrovascular invasion is an advancedstage malignancy that may benefit from targeted immunotherapy and subsequent surgical resection [26], but the comparison between surgery following neoadjuvant targeted immunotherapy and upfront surgery in terms of short-term postoperative complications and long-term prognosis remains unclear. Therefore, this multicentered study aimed to investigate the safety and efficacy of targeted immunotherapy followed by surgical resection for HCC with macrovascular invasion, taking upfront surgery as control.…”
Section: Introductionmentioning
confidence: 99%